Cooxidation of Aromatic Anils and Oxalic Acid by Chromic Acid in Aqueous Acetic Acid Medium - SRINIVASAN, R.; MOHAMED KASIM, A.N. (Asian Journal of Chemistry, 2010)
The kinetic study of the oxidation of aromatic anil and its five derivatives in presence of oxalic acid by chromic acid in aqueous acetic acid medium has been studied. The reaction involves three electron transfer due to conversion of Cr(VI) to Cr(III). The cooxidation reveals the first order kinetics for the oxidant Cr(VI), fractional orders (0.50) and (0.76) for substrate and oxalic acid, respectively. A suitable mechanism and activation parameters have been computed.